Efforts to Strengthen Parenting Competency of Parents In Child Rearing at the Tunas Ceria Posyandu In Toyomarto Village, Singosari District, Malang Regency - Abidin, Frita Idkhariza; Sopingi, Sopingi; Purnamasari, Ica (Proceedings Series of Educational Studies, 2024)
Parenting competency refers to the ability of parents encompassing knowledge, skills, and attitudes in child-rearing. This study aims to (1) describe the understanding of parenting among parents of students at Taman Posyandu Tunas Ceria, (2) describe the implementation process of the parenting program by Taman Posyandu Tunas Ceria, and (3) describe the efforts to strengthen parenting competencies undertaken by parents of students at Taman Posyandu Tunas Ceria. This research employs a qualitative approach with a case study type. Data were collected through observation, interviews, and document studies. The researcher analyzed the data through stages of data reduction, data presentation, and drawing conclusions. Data validity was ensured using source and technique triangulation. The results indicate that (1) parents' understanding of parenting is at the stage of extrapolating material application into their lives, (2) the implementation process of the parenting program involves several stages including discussions between facilitators and parents, facilitators studying the issues and finding speakers, and the parenting program being conducted according to parents' learning needs, and (3) efforts to strengthen parenting competency include self-learning, sharing with facilitators and other parents, and participating in the parenting program activities organized by Taman Posyandu Tunas Ceria.